PENGARUH PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PENGENTASAN KEMISKINAN DI KECAMATAN SEPAUK KABUPATEN SINTANG - Yuni Sarifah Fitri; Maria Ulfa; Bambang Genjik (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine whether there is an influence of the Family Hope Program (PKH) on poverty alleviation in Sepauk District, Sintang Regency. The method used in this research was descriptive method with the form of a study of relationship studies. The population in this study was 1,455 with a sample of 94 families. Data collection used was indirect communication (questionnaire) and documentary studies. The result revealed that 1) the percentage of family expectation program variables in the District of Sepauk Sintang District amounted to 74.23% classified as the high category, 2) the percentage of poverty alleviation variables in the District of Sepauk Sintang District amounted to 82.28% classified as very high category, 3 ) t_count of 4,457 which is greater than the value of ttable 1,989 so that Ha is accepted and Ho is rejected which means there is an influence between the Family Hope Program (PKH) on poverty alleviation. The coefficient of determination ( ) showed a figure of 0.178, so the percentage of the effect of the family of hope program on poverty alleviation was 17.8%.Keywords: Family Hope Program (PKH), Poverty Alleviation, Social Assistance.